2014
DOI: 10.1063/1.4901257
|View full text |Cite
|
Sign up to set email alerts
|

Coplanar switching of polarization in thin films of vinylidene fluoride oligomers

Abstract: Switching characteristics of vinylidene fluoride oligomer thin films with molecular chains aligned normal to the substrate and exhibiting a preferential in-plane polarization have been investigated using coplanar geometry of inter-digital electrodes via high-resolution piezoresponse force microscopy. It has been shown that in-plane switching proceeds via non-180° rotation of dipoles mediated by non-stochastic nucleation, expansion, and coalescence of domains. As-grown multidomain configuration is found to be s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…As one of the most studied electro‐optical materials, inorganic ferroelectrics have found a wide range of applications, ranging from sensors and actuators to optical and memory devices . In the past decade, a few organic–inorganic hybrid systems were also found to exhibit excellent ferroelectricity .…”
Section: Methodsmentioning
confidence: 99%
“…As one of the most studied electro‐optical materials, inorganic ferroelectrics have found a wide range of applications, ranging from sensors and actuators to optical and memory devices . In the past decade, a few organic–inorganic hybrid systems were also found to exhibit excellent ferroelectricity .…”
Section: Methodsmentioning
confidence: 99%
“…For example, the electrical properties of molecules can be used to build a variety of electronic components, such as transistors, rectifiers, and amplifiers. Another promising application is the use of molecules to mimic electrical switches. Upon applying an electric field, it has been found that some molecules can change from a high to a low conductance state due to the bistability of the molecule. Although most of these studies have been performed using a scanning tunneling microscope (STM), very few studies have examined bistability in a two-terminal device at room temperature. Fabricating and effectively controlling the behavior of these molecular switches requires a fundamental understanding of the electronic transport across a metal–molecule–metal junction and of the origins of the bistability of the molecules. …”
mentioning
confidence: 99%
“…Further, the phase difference induced by the piezopotential is very close to 180° (Figure S7b). 42 Such a feature, already observed in LB and LS film of the known ferroelectric polymer P(VDF-TrFE) 43,44 suggests the ferroic nature of the film. Besides, piezoelectric feature proposes such a material as an interesting IFL in organic photovoltaic devices.…”
Section: Polarizability Modulation and Opto-electronics Behaviormentioning
confidence: 90%